Multidimensional analysis of honey from Eastern Anatolia (Kars): Pollen spectrum, physicochemical properties, and antimicrobial activity. - Salih Akpınar; Neslihan Mutlu (PLoS ONE)
This study investigates the physicochemical properties, pollen composition, and antimicrobial activity of honey samples collected from Kars province, Türkiye. A total of 30 honey samples were analyzed for moisture content (13.9-18.0%), pH (3.44-3.92), electrical conductivity (0.138-0.343 mS/cm), free acidity (13.9-31.5 meq/kg), diastase activity (4.93-28.1 DN), hydroxymethylfurfural (HMF) levels (3.5-37.1 mg/kg), sugar profile (fructose: 32.8-41.0%, glucose: 26.2-32.6%, sucrose: 0.1-2.7%, maltose: 1.4-2.7%), and proline content (288.87-1272.9 mg/kg). Pollen analysis identified 52 taxa from 30 botanical families, with Fabaceae, Boraginaceae, Lamiaceae, Asteraceae, and Brassicaceae being the most dominant. Of the honey samples, 27 were classified as multifloral and 3 as unifloral. Total pollen counts per 10 g (TPC-10 g) of honey ranged between Group II and Group V categories (2000 to > 100000 grains). The antimicrobial activity of the honey was evaluated against Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus, Enterococcus faecalis, and Bacillus subtilis using the agar well diffusion method. Inhibition zones ranged from 11 ± 0.55 mm to 24 ± 1.2 mm, with greater efficacy observed against Gram-positive bacteria. Significant correlations were found between diastase activity and Staphylococcus aureus (r = 0.704, p < 0.01) and Enterococcus faecalis (r = 0.518, p < 0.01), as well as between proline content and Klebsiella pneumoniae (r = 0.454, p < 0.05), Pseudomonas aeruginosa (r = 0.384, p < 0.05), Staphylococcus aureus (r = 0.439, p < 0.05), and Bacillus subtilis (r = 0.435, p < 0.05). The sugar composition complied with international standards, with fructose and glucose being the predominant sugars. HMF levels remained within acceptable limits, suggesting appropriate storage and processing conditions. Overall, the findings highlight the high quality and antimicrobial potential of Kars honey, supporting its value as a natural and functional food product.